Faktor Yang Mempengaruhi Internet Financial Reporting (Ifr) Pada Pemerintah Kabupaten/Kota Di Sumatera Barat - Evin Amaliyah Masra; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to examine the effect of legislative size, income per capita, and regional expenditure on the internet financial reporting in districts / cities of West Sumatera province for the year of 2016-2018. This research uses agency theory and signalling theory. The number of samples used in the study as many as 19 local government website is calculated based on purposive sampling. Types of data are collected using secondary data. The results of this research suggest that income per capita and regional expenditure have a positive effect on the practice of internet financial reporting. Meanwhile, legislative size has no effect against internet financial reporting practices in the local government website